Implementation of Balanced Scorecard in Geological Exploration Project Performance Evaluation - Hasan, Hamida; Hasan, Haslindah (Amsir Management Journal, 2024)
This study examines the application of the Balanced Scorecard in evaluating the performance of geological exploration projects through a qualitative approach. The study explores how the four perspectives of the Balanced Scorecard (finance, customers/stakeholders, internal business processes, and learning and growth) can be tailored to the unique characteristics of geological exploration projects. The results show that the Balanced Scorecard, when appropriately adjusted, can be an effective tool for comprehensively evaluating performance, managing risk, and aligning short-term goals with long-term strategies. Although its implementation faces challenges, especially in determining the appropriate metrics, the Balanced Scorecard has proven to help companies manage the complexity and uncertainty inherent in geological exploration projects, while still considering long-term sustainability aspects.